2018
DOI: 10.2337/db17-1124
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Oxygen Improves In Vivo Mitochondrial Oxidative Phosphorylation Flux in Sedentary Obese Adults With Type 2 Diabetes

Abstract: Type 2 diabetes is associated with impaired exercise capacity. Alterations in both muscle perfusion and mitochondrial function can contribute to exercise impairment. We hypothesized that impaired muscle mitochondrial function in type 2 diabetes is mediated, in part, by decreased tissue oxygen delivery and would improve with oxygen supplementation. Ex vivo muscle mitochondrial content and respiration assessed from biopsy samples demonstrated expected differences in obese individuals with ( = 18) and without ( =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…Our findings indicate that the greater mitochondrial activation induced when breathing hyperoxia compared to normoxia during cycling did not induce greater mitochondrial biogenesis and/or intrinsic function. It has been shown that hyperoxia does not increase in vivo mitochondrial respiration during exercise in obese untrained but only in patients with type II diabetes with impaired ex vivo mitochondrial respiration (Cree-Green et al, 2018). The unchanged in vivo mitochondrial respiration in obese untrained but overall healthy individuals when breathing hyperoxia can be explained by a lower mitochondrial O 2 affinity (p50 mito ), a novel mechanism regulating oxygen diffusion from microvessels to muscle mitochondria with direct effects on oxygen consumption (Cardinale et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that the greater mitochondrial activation induced when breathing hyperoxia compared to normoxia during cycling did not induce greater mitochondrial biogenesis and/or intrinsic function. It has been shown that hyperoxia does not increase in vivo mitochondrial respiration during exercise in obese untrained but only in patients with type II diabetes with impaired ex vivo mitochondrial respiration (Cree-Green et al, 2018). The unchanged in vivo mitochondrial respiration in obese untrained but overall healthy individuals when breathing hyperoxia can be explained by a lower mitochondrial O 2 affinity (p50 mito ), a novel mechanism regulating oxygen diffusion from microvessels to muscle mitochondria with direct effects on oxygen consumption (Cardinale et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…As with previous reports, we observed lower oxidative flux in people with T2D. We tested whether the difference in oxidative flux was due to lower oxygen availability using supplemental oxygen and observed that the supplemental oxygen improved oxidative flux in people with T2D, but not in control participants [ 97 ]. These data support the overall working model that perfusion heterogeneity and local muscle hypoxia contribute to in vivo impaired mitochondrial function in people with T2D.…”
Section: Blood Flow and Muscle Oxygenation In T2dmentioning
confidence: 64%
“…The interrelations of blood flow, metabolism and performance have been recently extensively discussed by Lewis et al (2019). There is clinical evidence to support these contentions available in patients with PVD subjected to revascularization and in metabolic diseases (type 2 diabetes) in which patients breathed hyperoxic air (Cree-Green et al, 2018;West et al, 2012). Modulation of the available oxygen had measurable effects on the production of ATP, more than doubling production in the PVD patients.…”
Section: Consequences For Muscle Metabolism and Performancementioning
confidence: 99%